Servicescape: the impacts of physical surroundings on customers in Amanah Saham Nasional Berhad, Melaka Branch / Muhammad Nur Ikhsan Mohd Sefian - Mohd Sefian, Muhammad Nur Ikhsan (Faculty of Business and Management, 2009)
Services play the major roles in delivering the product to the customers in proper manner. Services marketing can be classified as the same strength like the product marketing and its compliment to each other. In this study, it will discuss one of the important area within services marketing that can give huge impacts in evaluating overall service delivery performance. Services cape consist of different elements like ambient elements, space elements and sign or symbols. These elements have its own sub sector that describe different approach in determining the impacts the customers as well as the employees of the organization. This study will take the Amanah Saham Nasional Berhad, a unit trust company Melaka branch that involve in fully service environment as the pilot organization to be examine and evaluate. Most of the customers have affected by physical environment during the process of service delivery. The attributes that give high impacts on customers are music, arrangements, wall decoration, waiting and queuing facilities. The are a lots of suggestions from this study and might be useful for future improvement.